Clarifying Sustainable Development Concepts Through Role-Play. (December 2015) - Blanchard, Odile; Buchs, Arnaud
Purpose. The article aims at assessing theeffectiveness of arole-play in addressing two concerns: clarifying theconcept of sustainable development andteaching sustainable development issues . Method. The effectiveness of the role-play is gauged by surveying students to reveal how the game matches a set of significant learning criteria defined by Fink. Structure of the article. First, our article provides a short overview of how theconcept of sustainable development has emerged and spread over time. Second, in order to assess the learning potential of our role-play, we examine how it addresses the six components of Fink'staxonomy of significant learning : (a) foundational knowledge, (b) application, (c) integration, (d) human dimensions, (e) caring, and (f) learning how to learn. Results. The assessment shows that our role-play is highly praised by the players as it not only brings themfoundational knowledge, but also allows them to enhance manyskills . Conclusion. The framework of the role-play contributes to educating about sustainable development as well as educating for sustainable development.